Perception of dental students and laypersons to altered dentofacial aesthetics - Aldhorae, Khalid; Alqadasi, Basema; Altawili, Zainab M.; Assiry, Ali; Shamala, Anas; Al-Haidari, Salah addin (Wolters Kluwer Medknow, 2020)
Aims and objectives: The aims of the study were to comprehensively assess the perception of altered dentofacial aesthetics between dental students and laypersons and to identify the threshold where different variables such gender and clinical training impair dentofacial attractiveness. Materials and methods: Ten photographs were digitally manipulated involving three facial, two smile, four dental, and one gingival components. Fifty images were randomized and rated according to attractiveness by two groups dental students which subdivided into preclinical students and clinical students, and laypersons. The participants evaluated the original and manipulated images using a visual analog scale. The responses were then analyzed using Mann-Whitney U test. Results: The results showed threshold levels of noticeable differences between varying levels of discrepancy. The overall perception of aesthetics was high among dental clinical students with the highest perception toward facial profile and the lowest toward gingival margin height. Of the respondents, no differences were found in the perception between male and female participants. Dental students perceived aesthetic components more accurately than laypersons. Conclusion: Dental students group had a better perception of dentofacial aesthetics than included laypersons. Unlike gender, clinical training has a substantial positive effect on the assessment of beauty. Dental students sub divided into dental preclinical students and dental clinical students (clinical training is a variable of all subgroups).